Oral mucosal involvement in Langerhans- cell histiocytosis: long-term follow-up of a rare case - ALKAN, ALPER; KILIÇ, Eser; Er, N.; Mavili, E.; Alkan, A.; Gunhan, O. (My University, 2011)
Langerhans cell histiocytosis (LCH) is a rare disease where different organs and systems may be affected. Oral involvement generally consists of mucosal ulceration associated with lesions of the underlying bone. Many reports exist about the misdiagnosis of this disease. Various symptoms may lead the clinician to an incorrect diagnosis, especially with multiple organ involvement. Oral manifestations are common, and dentists should be aware of this disease and evaluate intraoral findings accordingly. This study presents an LCH case characterized by oral mucosal ulcerations with no involvement of the underlying bone. A definitive diagnosis was made by open biopsy from the oral mucosa.